De la production à l’usage de la mesure, quelle appropriation par deux entreprises industrielles ? Pour quelle prévention des TMS ? - Jean-François Thibault; Xavier Merlin; Alain Garrigou (Perspectives Interdisciplinaires sur le Travail et la Santé)
This paper, produced from interventions conducted over several years in two industrial companies, namely a large manufacturing company in the automotive sector and an SME in the pharmaceutical sector, provides feedback on the generation and use of measurements in MSD prevention. After an introduction to the problem and a quick presentation of MSD prevention using the Muska®MSD tool, we analyzed the research feedback based on its impacts in terms of adaptation in the two companies. We compared how they incorporated the generation and the use of measurements through the Muska®MSD tool based on four criteria identified as necessary for sustainable MSD prevention. Finally, we concluded with the roles allocated to the generation and use of measurements so as to ensure sustainable MSD prevention.